An experimental investigation on the impact of brine composition on silica solubility at high temperature - Ahmed, F.A. (North Atlantic University Union, 2016)
The theory of silica-water system or silica solubility is quite complex as it involves dissolution, polymerization and precipitation processes to form the silicate scale. The type and amount of silicate scale observed is dependent on several factors including pH, salinity, magnesium concentration, and the ratio of calcium to magnesium. This paper describes the impact of some factors including brine salinity and composition on silica solubility using crash quartz sandstone core samples. Synthetic brine with different salinities ranged between 20,000ppm to 60,000ppm were utilized to determine the change in soluble silica at 80Â°C. The amount of silica dissolved from the sandstone sample was measured using Silicomolybdate method and validated using Energy Dispersive X-RAY and X-RAY Diffraction techniques. The results clearly showed that the composition of the brine has a significant effect on the silica solubility. The amount of silica dissolution increased from 41.0mg/L to 67.8mg/L when the brine salinity increased from 20,000ppm to 60,000ppm, due to the increasing in salt contents of the brine. It was also observed that the addition of magnesium and calcium with ratio 1:1 to the brine would greatly affect the silica solubility. This has been confirmed by analyzing the samples before and after saturation by the use of Energy Dispersive X-RAY. Â© 2016, North Atlantic University Union. All rights reserved.